Vitamin D-Binding Protein Directs Monocyte Responses to 25-Hydroxy- and 1,25-Dihydroxyvitamin D - Chun, Rene F. (The Endocrine Society, 2010)
Background: Serum 25-hydroxyvitamin D (25OHD) is a key factor in determining monocyte induction of the antimicrobial protein cathelicidin, which requires intracrine conversion of 25OHD to 1,25-dihydroxyvitamin D [1,25(OH)(2)D]. Both vitamin D metabolites circulate bound to vitamin D-binding protein (DBP), but the effect of this on induction of monocyte cathelicidin remains unclear. Methods: Human monocytes were cultured in medium containing 1) serum from DBP knockout (DBP(−/−)) or DBP(+/−) mice, 2) serum-free defined supplement reconstituted with DBP or albumin (control), and 3) human serum with different DBP [group-specific component [Gc]] genotypes with varying affinities for vitamin D metabolites. In each case, response to added 1,25(OH)(2)D(3) or 25OHD(3) was determined by measuring expression of mRNA for cathelicidin and 24-hydroxylase. Monocyte internalization of DBP was assessed by fluorescent tagging followed by microscopic and flow cytometric analysis of tagged DBP. Results: Monocytes cultured in DBP(−/−) serum showed more potent induction of cathelicidin by 25OHD(3) or 1,25(OH)(2)D(3) when compared with DBP(+/−) serum. Likewise, DBP added to serum-free medium attenuated 25OHD(3)/1,25(OH)(2)D(3) responses. Fluorescently tagged DBP showed low-level uptake by monocytes, but this did not appear to involve a megalin-mediated mechanism. Human serum containing low-affinity Gc2-1S or Gc2-2, respectively, supported 2.75-fold (P = 0.003) and 2.43-fold (P = 0.016) higher induction of cathelicidin by 25OHD relative to cells cultured with high affinity Gc1F-1F. Conclusion: These data indicate that DBP plays a pivotal role in regulating the bioavailablity of 25OHD to monocytes. Vitamin D-dependent antimicrobial responses are therefore likely to be strongly influenced by DBP polymorphisms.